Designing Cluster Development-based Entrepreneurial School Model in Tourism Sector for Vocational High School - Sukardi, Sukardi; Wildan, Wildan; Fahrurrozi, Muh. (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aimed at obtaining the design of an entrepreneurial school model for vocational high school based on an effective cluster development in tourism sector to strengthen the competitiveness of vocational high school graduates. This study applied research and development procedures and design based research (DBR) models which were integrated with constructivistic design principles. The procedures involve evaluation and determination of regional supremacy as a leading commodity / industry; development of design and product model for entrepreneurial school cluster-based model; and a reflection and experimental process to get the final product model. The collection of data on developing process was taken through in-depth interviews and focus group discussions (FGD) in schools, governments, industrial world groups, and other stakeholders. In addition, the questionnaire was also used to get the feasibility of the design by involving experts in the areas of tourism, economy, education, and development. The overall data were then analyzed qualitatively. The components of the entrepreneurial school model produced involve audience, content, procedures, and evaluations.Â The design produced learning outcomes, an integrated entrepreneurial curriculum, standardized documents and standard operational procedures, entrepreneurship school management modules. The expert analytical test shows that the overall design and product model are very good.